Commemorating Rokeya Sakhawat Hossain and contextualising her work in South Asian Muslim feminism - Hasan, Md. Mahmudul (International Islamic University Malaysia, 2013)
Colonial Muslim South Asia had two leading cultural centres: Bengal and North India. As part of the far-reaching reformist movement during the colonial period and beyond, intellectual work from these two places included a powerful segment of feminist writing which has remained the harbinger of the women’s rights movement among Muslims of this region. It is important to give research attention to South Asian Muslim writers, many of whom have been marginalised mainly because of the dominance of, and sometimes overriding and disproportionate focus on, their Hindu counterparts. Against this background, this article discusses the life, incredible commitment, sacrifice and feminist accomplishments of Rokeya Sakhawat Hossain (1880-1932). It will also contextualise her ideas in the broader South Asian Muslim feminist tradition.